PERAN PEMBIMBING KEMASYARAKATAN DALAM UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Samuel Saut Martua Samosir (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2017)
Law Number 11 of 2012 concerning the Juvenile Criminal Justice System essentially regulates the entire process of the settlement of juvenile facing legal problems which started the investigation stage to the stage of supervision after sentenced. If one’s refers to the old paradigm that the criminal justice system contained in the Criminal Procedure Code which has put four components of criminal justice, namely the police, prosecutors, courts and the Penitentiary, which are acted as the integral system, but in fact there exists the Penitentiary advisor also. So, It is necessary to analise in how to find out and to understand the position of Penitentiary advisor in a juvenile criminal justice system in particular. In sum, based on a broad range of function of the Penitentiary advisor, which spread from the investigation to the decision on Juvenile sentence, the Advisor Community has the seminal position. The opinion aforementioned describe that there are some issues that need to be understood regarding the formal understanding on how the actual existence of the Penitentiary Supervisor and the report based on the public research or the consideration of Penitentiary advisor with regard to law enforcement officers, especially in the juvenile justice system. In sum, this writing should be valuable not only in order to constitute Juvenile Criminal System actual aims and purposes, but also the extent of the implications of the report of the public research to the decision in juvenile criminal system.Keywords : Penitentiary Advisor, Juvenile , Criminal Justice System